Analisis Pengembangan Desa Wisata untuk Keberlanjutan Petani Strawberry di Desa Wisata Pandanrejo Menggunakan Metode Participatory Rural Appraisal (PRA) - Deti Rahmawati; Soedarso; Arfan Fahmi (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2023)
The concept of Village-City Development's hegemony is being clarified invarious media outlets, necessitating periodic reviews to strike a balancebetween the two. The harmonization of village development is evident in therapid improvement and transformation of villages, exemplified by theemergence of tourist villages. Among these, Pandanrejo Tourism Villagestands out, offering strawberry barn tourism that has been operational sincelate 2018. This tourism destination not only showcases strawberry gardensand products but also provides educational tours related to strawberries. Tosupport the success of tourism villages, efforts can be made by mapping thecommunity's potential and needs, which will inform the developmentprograms aimed at empowering the local populace. The research undertakenin this study employed the Participatory Rural Appraisal (PRA) method,which ensures that the people of Pandanrejo Tourism Village are not mererecipients of top-down programs, but active participants in designing bottomup development initiatives. This approach encourages the community'sinvolvement throughout the development process. The study encompassesseveral stages of analysis, allowing village communities to actively participatein identifying social problems and their root causes, devising solutions, andsubsequently formulating programs. These programs will receive budgetarysupport and be implemented based on principles of cooperation,empowerment, and community independence.